The surgical treatment of primary hyperparathyroidism: a 20 year experience. - Coffey, R J (1977)
Analysis of a series of 200 surgically treated cases of primary hyperparathyroidism was carried out in an effort to identify not only the changing clinical patterns and improved diagnostic methods but also to assess the long term results of our conventional operative methods in light of recent reports of a high incidence of diffuse hyperplasia and a high recurrence rate when surgery is restricted to removal of the adenoma. As reported by others the "chemical diagnosis" of primary hyperparathyroidism, the clinical setting in which unsuspected hypercalcemia is demonstrated on routine blood analysis, accounts for the majority of diagnoses today. Impending or actual "parathyroid crisis" has been observed with alarming frequency. The use of the thiazide challenge test provides a useful diagnostic aid in many instances. The incidence of diffuse hyperplasia was 6% in this series while an adenoma was present in 88%. No instance of recurrence was observed in either the cases of adenomas or diffuse hyperplasia.